Combined therapy with prospidin and methotrexate in rheumatoid arthritis (12 months controlled study) - B. F. Nemtsov; O. V. Simonova; E. V. Benenson; N N Politova (Научно-практическая ревматология, 2003)
Objective. To study efficacy of combined therapy with prospidin (P) and methotrexate (MT) in rheumatoid arthritis (RA). Methods. 60 pts with RA (53 female and 7 male) aged 20 to 72 years were included. The mean disease duration was 5,6 years. 51 patients had 2 and 9-3 degree of RA activity. The pts received P 200-300 mg/week intravenously dropwise with 200 ml of 5% glucose solution during 4 weeks. Intramuscular injections of MT 10 mg/week were given at the third day after the administration of P. Maintenance treatment included P 100-200 mg/week and MT 10 mg/week. Results. Combined therapy provided fast and marked clinical effect in pts with unfavorable variants of RA. 50-70% improvement according to ACR criteria was achieved in 50% of pts received P and MT during 12 months. Amelioration of some laboratory indices of RA activity was also noted. Side effects of combined therapy were reversible and not severe. They led to discontinuation of therapy only in 14,8% .